RIL commissions the world’s largest and fully integrated Refinery Off-Gas Cracker at Jamnagar - Reliance Industries Limited (2022)
"RIL commissions the world’s largest and fully integrated Refinery Off-Gas Cracker at Jamnagar, joining the distinguished league of top 5 petrochemical producers globally."